DRAMATURGI PARA MODEL DI KOTA DENPASAR DALAM KEHIDUPAN SEHARI-HARI - Riana Sari, Meidiawati; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2021)
This research analyzes how technological development have impact on various aspects of human’s life and create diverse professional fields in Denpasar city, social media instagram as a forum to develop potential as a model. An instagram celebrity generally has a strong influence to their followers. This makes the celebgrams will use the opportunity to benefit from endorsement. The method is qualitative-descriptive explanative type. The theory is dramaturgical of Erving Goffman explaining that everyday’s life is a stage setting and humans are actors who act to impress audiences. Human have three stages, frontstage, middlestage, backstage. On frontstage, models on their personal instagram tend to display a very perfect self-image, and good behavior. But when they are in backstage they tend to be themselves, be outspoken and release all attributes that they aspires to on social media, middlestage is the place where models prepare to improve their appearance on the frontstage. Keywords : Model, Kota Denpasar, Dramaturgi, Sosial Media